Pengaruh Return On Investment (Roi) Dan Debt To Equity Ratio (Der) Terhadap Harga Saham (Studi Empiris Pada Perusahaan Teknologi Yang Terdaftar Di Bursa Efek Indonesia Tahun 2020 - 2022) - Putri Amelia Mailensun; Retha Tesalonika S; Ratih Kusumastuti (Pusat Riset dan Inovasi Nasional, 2023)
Financial reports can be used as an illustration to assess how a company is performing, including in terms of investment. This study aims to determine the effect of return on investment (ROI), debt to equity ratio (DER) on stock prices. The population in this study are technology companies listed on the Indonesia Stock Exchange (IDX) in 2020-2022. Selection of the sample using purposive sampling, namely using a sample with certain criteria. The number of samples is 18 companies. The data analysis method used is linear regression analysis with the help of the IBM SPSS Statistics 25 program. The results of this study indicate that Return On Investment has a significant effect on stock prices, Debt To Equity Ratio has no effect on stock prices.